Representations and publications on the Argentinian gaucho in the thirties. Between national identity, literary ield and business strategies. (2015)
During the thirties, in Argentina, there was a rising concern for deining the “national being” and consolidating an identity that considered itself to be threatened by mass immigrations and foreign ideological currents. In this context, the proile of the gaucho was utilized by several publications which acknowledged the evocation of country people from la pampa as the symbolic reference for an “essence of Argentina”. This article studies the composition and circulation of the gaucho imaginary, in years previous to governmental intervention on these topics. Focus is made upon the constitution and expansion of literature in Buenos Aires through periodical publications which, in different measures,proposed deinitions for “gaucho” and “tradition”. In this study, stress is set upon the marketing approachapplied by several businessesto expand and legitimize their products in new markets.